Нові технології укладання та контролю стану шахтних рейкових колій - Денищенко, О. В.; Барташевський, С. Є.; Скляров, А. В.; Бедило, Т. А. (My University, 2017)
Проведено аналіз сучасного стану рейкових колій вугільних шахт та виділено основні чинники, що впливають на їх стабільність. Запропоновані технічні рішення, що дозволять підвищити термін служби елементів верхньої будови шляху, та засоби контролю його стану в процесі експлуатації.

Проведен анализ современного состояния рельсовых путей угольных шахт и определены основные факторы, влияющие на их стабильность. Предложены технические решения, позволяющие повысить срок службы элементов верхнего строения пути, и средства контроля его состояния в процессе эксплуатации.

Both experimental and theoretical research concerning geometric irregularities of railtrack performed by the authors in mine workings of Western Donbas mines made it possible to obtain reliable information on actual state of rail which analysis points to substantial deviation of basic parameters from standard ones. Objective of the work is to improve reliability of mine railtrack basing upon the development and implementation of innovative engineering solutions.
New technologies of conclusion and control of the state of mine claotype tracks
Keywords: a mine; rail track; polymeric sleeper; rail fastenings; grading of track; engine curent; вугільна шахта; угольная шахта; рельсовая колея; рейкова колія; техническое решение; технічне рішення